2019
DOI: 10.1002/tl.20345
|View full text |Cite|
|
Sign up to set email alerts
|

Mobilizing a Culture Shift on Campus: Underrepresented Students as Educational Developers

Abstract: This chapter describes the transformative potential of positioning students from underrepresented groups as educational developers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
9
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 17 publications
1
9
0
2
Order By: Relevance
“…Beyond corroborating increasingly common findings about the benefits of pedagogical partnership for participating students from equity-seeking groups (e.g., Cook-Sather & Agu, 2013;Colón García, 2017; for detailed reporting of these results from the present study see Cook-Sather, 2018, 2020de Bie et al, 2019), this article builds on preliminary study findings reported elsewhere (Cook-Sather, Krishna Prasad et al, 2019) by offering further insight into partnership's capacity to contribute to equitable classroom practices. As participants noted, key dimensions of this potential impact include the mobilization of student partners' equity-specific expertise to promote faculty reflection and concrete shifts in approaches to teaching; however, there are also notable challenges to advancing equity through partnership.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Beyond corroborating increasingly common findings about the benefits of pedagogical partnership for participating students from equity-seeking groups (e.g., Cook-Sather & Agu, 2013;Colón García, 2017; for detailed reporting of these results from the present study see Cook-Sather, 2018, 2020de Bie et al, 2019), this article builds on preliminary study findings reported elsewhere (Cook-Sather, Krishna Prasad et al, 2019) by offering further insight into partnership's capacity to contribute to equitable classroom practices. As participants noted, key dimensions of this potential impact include the mobilization of student partners' equity-specific expertise to promote faculty reflection and concrete shifts in approaches to teaching; however, there are also notable challenges to advancing equity through partnership.…”
Section: Discussionsupporting
confidence: 80%
“…Given this backdrop, the current discussion seeks to build on existing research, and on a preliminary consideration of ideas about broader change in practice arising from our data (Cook-Sather, Krishna Prasad et al, 2019), by attending to students' perspectives on how pedagogical partnership might contribute to equity-related outcomes that affect students beyond those immediately involved. We also note particular challenges that arise for equity-seeking students working in partnership, considering how these both affect individual participants and mediate partnership's capacity to contribute to equity on a broad scale.…”
Section: The Potential Of Partnership To Contribute To Equity In Teaching and Learningmentioning
confidence: 99%
“…Yet students have essential insights without which we cannot develop the most effective pedagogical approaches (Cook-Sather, 2019;Felten et al, 2019;Healey et al, 2016;Marquis et al, 2016;Reynolds et al, 2019). Furthermore, when students, particularly those typically underrepresented in and underserved by postsecondary institutions, are positioned as educational developers, they can mobilize a culture shift on campuses toward greater equity, inclusion, and justice (Cook-Sather, Krishna Prasad et al, 2019;de Bie et al, 2021). Takayama et al (2017) have argued that such a culture shift can be advanced through strategic multi-level leadership that can start at the macro, meso, or micro level.…”
mentioning
confidence: 99%
“…• institutions should adopt a more holistic, comprehensive approach to supporting teaching and learning for diverse groups of learners. students-students of color and other underrepresented and underserved groups in particular-as "holders and creators of knowledge" (Delgado Bernal, 2002, p. 106) and, specifically, as co-creators of understandings and practices of postsecondary education that are responsive to a diversity of students (Cook-Sather & Agu, 2013;Cook-Sather, Krishna Prasad et al, 2019;de Bie et al, 2019).…”
mentioning
confidence: 99%
See 1 more Smart Citation